Implementasi Pemerintahan Kota Depok Dalam Upaya Meningkatkan Ekonomi Masyarakat Menurut Pasal 33 UUD '45 - Evi Novita; Surahman Surahman; Dessy Damayanthi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
The study aims to find out how the city government implementation developent of depok in an effort to boost the public economy according to article 33 of 1945 of Islamic studies. The writer wants to know some factors that are an impediment and success in the Depok city’s efforts to boost the economy is good. The method of research is using a qualitative method, as for this research instrument is an interview, observation, documentation, a printed purpose associated with the title of the thesis that then gained a validity of the data. From the data gathered on the results of the study above. Thus the write concluded that the separate town of Depok from the town of Bogor was in the economic structure, development, transportation, education, natural resources and human resources and technology can flourish well.